2019
DOI: 10.5688/ajpe7367
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Canadian Doctor of Pharmacy Student Experiences in Non-Traditional Student-Preceptor Models

Abstract: Objective. To describe students' experiences and perceptions of non-traditional student-preceptor learning models and evaluate the effectiveness of these models on students' learning experience. Methods. Pharmacy students who had completed at least one experiential rotation with a nontraditional learning model participated in semi-structured interviews. Models included peer-assisted learning (PAL; two or more students of same educational level), near-peer teaching (NPT; one or more junior students with one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Peer learning is a good opportunity to equip learners with education-related skills, such as providing feedback (Tai et al 2017). These education skills may also support patient education; indeed, students have reported that their clinical communication skills have improved through participation in peer learning (Tai et al 2016b;McIntyre et al 2019).…”
Section: Educational Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peer learning is a good opportunity to equip learners with education-related skills, such as providing feedback (Tai et al 2017). These education skills may also support patient education; indeed, students have reported that their clinical communication skills have improved through participation in peer learning (Tai et al 2016b;McIntyre et al 2019).…”
Section: Educational Benefitsmentioning
confidence: 99%
“…Peer learning may also provide much wanted social and academic support (Chou et al 2011;Vuckovic et al 2019;McIntyre et al 2019;McPake 2019), and may increase student self-confidence (Secomb 2008;Chojecki et al 2010;Ravanipour et al 2015). This is especially crucial in the transition to clinical learning environments (Masters et al 2013).…”
Section: Practical Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 The LLPM incorporates pharmacy learners into the workflow as "pharmacist extenders," allowing them to perform patient care activities while also creating opportunities for mentorship between learners. [7][8][9] The LLPM has demonstrated benefit on multiple fronts: reduced medication costs, improved patient satisfaction, and improved clinical outcomes. 7,10,11 The experiences of pharmacy personnel involved have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in demand has led institutions to explore more experiential teaching models. (Mcintyre et al, 2019) As described by (Myall, Levett-jones, and Lathlean, 2008) that the mentoring process helps students to organize and integrate concepts, prepare strategies to develop a better understanding of themselves as caregivers, and promote commitment to the profession. Snowden (2008) explained that through a constructive clinical learning environment with good guidance, students will find it easier to develop their self-confidence and competence as well as focus more on student learning needs.…”
Section: Introductionmentioning
confidence: 99%